(untitled) (Research, Society and Development, 2022)
Psychiatric care consists for many years in a treatment based on asylum care, this context changed with the Psychiatric Reform. From this, the logic of treatment to be based on extra-hospital services, and its user started to be attended within the social context, in the community. In this new process, the family becomes the main caregiver and lives with a person who was previously isolated in the hospitals. However, this care cannot affect the family environment, thus requiring monitoring and intervention with them. Therefore, the present work aims to investigate the burden of caregivers of users with psychological distress and consequences for their daily lives. The methodology used was a qualitative description, analyzing a semi-structured and semi-structured study with open questions, carried out with twenty-one caregivers, through a digital platform. As the importance of promoting care intervention policies are important in order to provide a better and quality life, in addition to allowing greater security in the performance of care.